Software Engineering and Formal Methods : SEFM 2015 Collocated Workshops: ATSE, HOFM, MoKMaSD, and VERY*SCART, York, UK, September 7-8, 2015. Revised Selected Papers - Bianculli, Domenico; Calinescu, Radu.; Rumpe, Bernhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes revised selected papers from the workshops collocated with the SEFM 2015 conference on Software Engineering and Formal Methods, held in York, UK, in September 2015. The 25 papers included in this volume were carefully reviewed and selected from 32 submissions. The satellite workshops provided a highly interactive and collaborative environment for researchers and practitioners from industry and academia to discuss emerging areas of software engineering and formal methods. The four workshops were: ATSE 2015: The 6th Workshop on Automating Test Case Design, Selection and Evaluation; HOFM 2015: The 2nd Human-Oriented Formal Methods Workshop; MoKMaSD 2015: The 4th International Symposium on Modelling and Knowledge Management Applications: Systems and Domains; VERY*SCART 2015: The 1st International Workshop on the Art of Service Composition and Formal Verification for Self-* Systems.
Automating Test Case Design, Selection and Evaluation -- Human-Oriented Formal Methods -- Modelling and Knowledge Management Applications: Systems and Domains -- Art of Service Composition and Formal Verification for Self-* Systems.
Keywords: Artificial intelligence; Computer software; Computer science; Database management; Information Systems Applications (incl. Internet).; Artificial Intelligence; Algorithm Analysis and Problem Complexity; Probability and Statistics in Computer Science; Computation by Abstract Devices; Database Management